ANALISIS PERBANDINGAN FRAMEWORK CODEIGNITER DAN LARAVEL DALAM PENGEMBANGAN WEB APPLICATION - Wini Muthia Kansha; Saherih; Muchlis (LPPM STMIK ANTAR BANGSA, 2023)
Abstract—PHP programming language is considered as one of the most used scripting languages in web application development. Programming trends have started to develop from using native to using frameworks. Professionals widely use programming using a framework because it has a standard framework that is common and clear to help developers build applications quickly. Codeigniter and Laravel are examples of PHP frameworks that are quite popular among web developers. A comparative analysis of the two frameworks was carried out from various perspectives, both in terms of framework structure and research experiments by making simple CRUD applications to measure the performance of the two websites. This comparison in terms of framework structure is intended so that it can be taken into consideration by web developers in choosing a framework that suits their needs in building web applications. From a simple experiment, in terms of performance, Laravel 8 is superior to CodeIgniter 4 with a not-too-significant difference.